Debt Maturity : Does It Matter for Fiscal Space? - Kim, Jun (IMF Working Papers; Working Paper ;, 2015)
This paper examines how debt maturity affects the debt limit, defined as the maximum amount of debt a government can afford without defaulting. We develop a model where investors are risk neutral, the primary balance is stochastic but exogenous, and default occurs solely due to the government's inability to pay. We find that debt limit is higher for long-term debt. Underlying this finding is the intrinsic advantage of long-term debt to price in future upside potential in fiscal outcomes in its current price. Such advantage makes long-term debt effectively cheaper than short-term debt at the margin, and leads to a higher debt limit. Simulation results suggest that the effect of debt maturity on debt limit could be substantial-particularly, if fiscal outcomes are subject to large uncertainty.